Analytical and finite element investigation on the thermo-mechanical coupled response of friction isolators under bidirectional excitation. Issue 106 (March 2018) - De Domenico, D.; Ricciardi, G.; Benzoni, G.
Abstract: The hysteretic behavior of friction concave isolators is affected by the variability of the friction coefficient experienced during a seismic event. This variability is a combined function of axial load, sliding velocity and temperature rise at the sliding surface, the latter being responsible for significant friction degradation. Experimental testing and corresponding numerical models are usually focused on the monodirectional performance of the friction isolators, although multi-directional paths occur in a real earthquake scenario. In this paper, the thermo-mechanical coupled (TMC) response of friction concave isolators when subjected to bidirectional excitation is investigated in both an analytical and a numerical framework. First, a simplified phenomenological model is presented that accounts for the friction degradation due to the distance traveled via a macroscale cycling variable, based on the assumption of a uniform heat flux at the sliding interface. Then, a more sophisticated numerical investigation is performed via a TMC finite element (FE) model. A customized subroutine has been developed and implemented into the FE code to account for the local variation of the friction coefficient due to the local temperature rise and sliding velocity. The mutual interaction between mechanical and thermal response is incorporated in the proposed computational approach: the friction-induced temperature rise on the contact points and the consequent friction degradation caused by heating phenomena are analyzed as two interconnected phenomena in a recursive fashion. The friction coefficient law at the sliding interface is adjusted step-by-step and is different from node to node on the basis of the temperature distribution. Validated against experimental data, the two proposed models are used within a parametric study to scrutinize some interesting features observed in the thermo-mechanical response of friction isolators. Abstract : Highlights: The thermo-mechanical behavior of friction concave isolators is analyzed. A thermo-mechanical coupled three-dimensional finite element model is set up. A simple analytical model is presented for comparison purposes. The temperature rise at the interface due bidirectional paths is investigated. Validation of the numerical models against experimental findings is carried out.